Diagenetic evolution of the Permian Tunas Formation, Claromecó Basin, Buenos Aires province, Argentina: its impact on porosity and reservoir characteristics (Latin American Journal of Sedimentology and Basin Analysis, 2024)
The foreland Claromecó Basin, located in the south-western sector of Buenos Aires province, Argentina, has a relevant economic and energetic interest due to the presence of coal layers contained in the  Permian Tunas Formation, which might be considered effective source rock for gas resource generation. This study aims to reconstruct the diagenetic evolution of the Tunas Formation at the Claromecó Basin (PANG 0001 and PANG 0003 wells) and determine how the diagenesis affected the reservoir quality. To this purpose, core samples of the Tunas Formation were analysed using a combination of micro petrographic analyses (transmitted light, QEMSCAN, cathodoluminescence), fluid inclusions studies, and petrophysical methods (conventional core analysis, CCA). The analysed sedimentary successions are composed of sandstones interbedded with mudrocks, carbonaceous mudrocks, tuffs, and coals. Sandstones are medium- to fine-grained, framework-supported, and moderate-to-well-sorted. Authigenic minerals are calcite and laumontite, with minor proportions of quartz and feldspar overgrowths and clay minerals (illite, muscovite, and chlorite). Porosity is of secondary type, generated by fracturing and dissolution of feldspars and carbonate cement. Porosity determined by optical, QEMSCAN, and CCA analyses ranges from 0.1 to 4 %, with a permeability varying between 10-3 and 10-6 millidarcies. Fluid inclusion studies were performed in sandstone cements and calcite and quartz veins. Primary, pseudo-secondary, and secondary aqueous and organic fluid inclusions were recognized. Organic fluid inclusions show green and light blue fluorescence, which indicates the presence of hydrocarbons. Homogenization temperatures of fluid inclusions obtained from microthermometry studies range from 124 to 200 °C in cements and 110 to 230 °C in veins. These temperatures confirm a metagenesis stage for the Tunas Formation, within the wet to dry gas window. Given the petrophysical characteristics of the analyzed levels, sandstones could be considered unconventional tight gas sandstone reservoirs. Obtained results point out that during early diagenesis, physical compaction and precipitation of carbonate cement are the principal factors that significantly reduce the primary porosity. Furthermore, in the mesogenesis stage, chemical compaction, calcite and zeolite cements precipitation, and quartz overgrowths further contribute to porosity loss. However, secondary porosity was produced during mesogenesis due to the dissolution of unstable grains and calcite cements caused by the action of acid fluids generated during the decomposition and maturity of organic matter. Additionally, secondary porosity was also generated by fracturing due to burial and tectonic stress and by the increased pore pressure during hydrocarbon generation and migration. The reservoir properties of the Claromecó Basin have been controlled mainly by diagenetic and tectonic processes that acted during the burial history of the basin. Clasts and cements composition also influenced diagenesis together with the presence of organic-rich rocks, which could generate hydrocarbons.
Keywords: diagenesis; reservoir; tight gas sandstones; QEMSCAN; Claromecó Basin